Implementasi Kebijakan Penyelenggaraan Lalu Lintas Di Cibiru Kota Bandung - Qori’atul Aulia Bayanillah; Rianamasri Yuianti; Risa Amalia Putri (Gunung Djati Conference Series, 2023)
The rapidgrowth in the number of motorized vehicles causes many problems to occur, such as traffic jams, accidents, and so on. The government has issued various policies regarding traffic, but traffic problems have not been resolved so far. The purpose of doing this research is to describe and understand more about how the implementation of traffic policy in Cibiru, Bandung city. The method used in this research is descriptive with a qualitative approach and interactive data analysis. The results of the research show that the implementation of traffic policies in Cibiru, Bandung City, is still not optimal and needs to be improved, especially in terms of providing infrastructure and outreach related to traffic policies.